Characterisation of ‘giant’ cysts of the potato cyst nematode, Globodera rostochiensis, present in potato fields in Kenya - Price, J.A.; Hunt, K.; Nyagah, N.; Orage, C.; Mwaura, O.; Haukeland, S.; Coyne, D.L.; Jones, J.T. (Brill, 2024)
Potato production in East Africa is seriously impacted by the potato cyst nematode (PCN), Globodera rostochiensis, where it has been recorded in at least three countries. In Kenya, it is widespread in all major potato-growing regions, often at very high densities. Consecutive cropping of potato on the same land and a sub-tropical climate have influenced PCN biology. For example, unusually large cysts have been regularly recovered. We have analysed the biological properties of these ‘giant cysts’. The giant cysts contained more eggs than those recovered from UK fields. Egg size did not differ from UK populations and there was no difference in overall lipid content or lipid profile in J2 from giant cysts, compared to control samples. The nematodes in giant cysts were also genetically indistinguishable from any other G. rostochiensis sampled. When grown under UK glasshouse conditions, the offspring of nematodes from giant cysts were no different in size from those grown from control cysts, indicating that gigantism is not a heritable trait and may simply reflect favourable conditions for PCN under Kenyan farming systems. To date, all the PCN tested from Kenya, including those from giant cysts, are avirulent on potato cultivars containing the H1 resistance gene.